Penerapan Aplikasi Banksampah.id Untuk Pengelolaan Sampah Menjadi Berharga - Achmad Sarwandianto; Lusi Ariyani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Efforts to improve the management of the RW 05 Waste Bank in Kreo sub-district are carried out through community service activities. One form of waste management in society is by utilizing waste banks. This waste bank collects household waste, sorts it, and resells it to other parties. Through the use of waste banks, waste can be processed into something that has economic value. In its management, waste banks use principles similar to the banking system, but on a smaller scale and are easier to run. Residents who live around the waste bank send their waste and their balance is recorded based on the economic value of the waste. The RW 05 waste bank management environment still faces a number of obstacles in its implementation. To improve waste bank management, this service program is carried out with various activities that provide economic value to residents. Efforts to improve waste bank management are carried out by implementing smash.id, in addition to providing assistance and training on creative products that use plastic waste. The aim of this step is to increase efficiency and progress in waste bank operations in rw.05 Kreo sub-district.